Effect of hydrogen peroxide - ammonium hydroxide treatment on the in-sacco degradability of crop residues - WADHWA, M; MAKKAR, G S (The Indian Journal of Animal Sciences, 2013)
Different levels of ammonium hydroxide were used (to replace sodium hydroxide) to make the media alkaline for hydrogen peroxide treatment of crop residues at varying time intervals. Best lignin breakdown, hemicellulose hydrolysis and in-sacco dcgradability were achieved by treating pearlmillet stalks with 1 % hydrogen peroxide containing 3% ammonium hydroxide (V /W) and 0.63% sodium hydroxide W/W) at 70Â°C for 72hr. Rice straw, sorghum and pearlmillet stalks were treated With 1% hydrogen peroxide containing either 4.2% sodium hydroxide (W/W) at 24’C for 6 hr (AHP-I) or 3.0% ammonium hydroxide (V/W) with 0.63% sodium hydroxide W/W) at 70’C for 72 hr (AHP-II). BOth the treatments resulted in significantly higher breakdown of cell-wall constituents and in-sacco degradability of crop residues as compared to the untreated ones. Between AHP-1 and 2 treatments, the latter resulted in significantly higher in-sacco degradability of all constituents except that of cellulose. Ammonium hydroxide used in hydrogen peroxide treatment improved nitrogen status and in-sacco dcgradsbility of cereal crop residues.